Evaluation of the Curriculum in the Special Classroom at Tedsabanjunghua School, Phatthalung Province - Noppakao Naphatthalung, (วารสารศึกษาศาสตร์ มหาวิทยาลัยทักษิณ, 2025)
The objective of the research was to evaluate the Special Classroom Curriculum of Tedsabanjunghua School, Phatthalung Province, using Hammond's Evaluation Model, which includes instructional, institutional, and behavioral dimensions. The target group consisted of the school principal, the deputy principal, five teachers involved in the Special Classroom Curriculum, and 70 Grade 9 students in the 2024 academic year. The research instruments used for data collection were a questionnaire to evaluate the Special Classroom Curriculum of Tedsabanjunghua School, Phatthalung Province, using a rating scale, and an interview to assess the same curriculum. Quantitative data were analyzed using descriptive statistics, including the arithmetic mean and standard deviation. Qualitative data were analyzed using content analysis. The results showed that: the instructional dimension was rated at a high level overall, the institutional dimension was also rated at a high level overall, and the behavioral dimension was similarly rated at a high level overall. Interviews with administrators and teachers about the evaluation of the Special Classroom curriculum at Tedsabanjunghua School, Phatthalung Province, revealed that the instructional dimension was effective, with appropriate class sizes, adequate lesson hours, and suitable learning materials and methods. The institutional dimension showed that students performed well academically and exhibited good learning behaviors, while teachers and administrators had sufficient qualifications and experience. The behavioral dimension highlighted that students effectively applied their knowledge to real-life situations, participated in learning activities, and developed language skills according to the set criteria, demonstrating positive attitudes and skills.